Treatment-Resistant Depression in Portugal: Perspective From Psychiatry Experts - Bessa, João M.; Carvalho, Serafim; Cunha, Inês B.; Fernandes, Milene; Matos-Pires, Ana; Neves, Rui; Oliveira-Maia, Albino J.; Santos, Susana; Santos, Vítor (Frontiers in Psychiatry, 2022)
Guidance about treatment-resistant depression (TRD) in Portugal is very limited, even though depression prevalence is among the highest in European countries. A questionnaire was conducted, followed by two advisory boards with seven Portuguese psychiatry experts, to characterize and discuss MDD and TRD epidemiology, diagnosis, patient journey, treatment options, and unmet clinical needs. Consensus was reached on the main issues. In daily practice, TRD can be defined as moderate to severe MDD episodes with insufficient clinical improvement after two antidepressant treatments, taken in adequate doses and duration. TRD diagnosis and treatment is mostly decided by psychiatrists at public hospitals. Treatment type and duration must be adjusted to characteristics of the patient and the depressive episode, including symptoms, number of previous episodes, comorbidities and previous treatment response and side effects. The most relevant objectives of TRD treatment are reaching response and remission, prevention of suicide, and improvement of quality of life, functionality, and well-being. Regarding pharmacotherapy, antidepressant switch occurs more frequently with non-response, while optimization, combination and augmentation are considered for patients with partial response. Psychotherapy should be considered in parallel to pharmacological treatment. Brain stimulation techniques are underused. Life-long treatment is required for recurrent or more chronic TRD episodes, but patient adherence is also poorer in these cases. In Portugal, TRD management is limited by lack of access to specialist care and to many treatment options. These aspects highlight that conventional pharmacotherapy don’t lead to remission in many patients and that optimization strategies are frequently necessary to achieve satisfactory treatment outcomes.